MEASURES OF PATIENT EXPOSURE TO IONIZING RADIATION DURING INTERVENTIONAL RADIOLOGY PROCEDURES - Opancina, Valentina D; Vojinovic, Radisa (Medicinski časopis, 2020)
Procedures used in interventional radiology brought considerable prosperity to patients when compared to traditional surgery. The negative aspect of interventional radiology procedures are effects of ionizing radiation on patients and the medical team that performs these procedures. The amount of ionizing radiation is defined as exposure, which is expressed in different measures. In order to present the effects of radiation, different types of units are used, since it is not achievable to quantify the stochastic and deterministic effects directly. Dose-area product, air kerma and fluoroscopy time are units that are used in interventional radiology, all of them are granted by the angiography machine. These units are used for the estimation of the entrance-skin dose and effective dose, which are associated with deterministic and stochastic effects, respectively. Finally, the main purpose is to obtain the absorption dose, which helps us to observe the patient exposure during interventional radiology procedures. The aim of this paper is to describe measures of patient exposure to ionizing radiation during interventional radiology procedures, using a thorough literature search.
Keywords: radiation exposure, interventional radiology, radiation dose, radiation measure, patients, review